Norwegian Stone Cathedrals of the End of the 11th — mid. 14th Centuries: Regional Features and European Context - Chemezova, Kseniia E. (Actual Problems of Theory and History of Art, 2017)
The architecture of Norwegian stone cathedrals of the end of the 11th — mid. 14th centuries is a unique page in the history of European architecture. Most of the studies devoted to the stone Norwegian cathedrals of that time rarely consider them as one phenomenon. This paper is the first research on the regiona lfeatures of the Norwegian cathedrals of that period. The purpose of the local investigation is the analysis of the major monuments of stone cathedral architecture of medieval Norway. The task of our research is to identify the main regional features of the Norwegian cathedrals at the end of the 11th — mid. 14th centuries based on the study of the experience of masters from Central and Western Europe. The paper makes an attempt to conduct a careful analysis and comparison of South-Western Norwegian cathedrals with the monuments of the so-called‘Hirsau school’.The paper studies five cathedrals of Norwegian medieval Bishoprics — St. Olav in Trondheim, cathedral of Christ in Bergen, St. Swithun in Stavanger, St. Hallvard in Oslo, and the Cathedral of Christ in Hamar. Their architecture shows the development of the ideas of the medieval building better than other monuments because they are the key monuments of stone architecture of Norway at that time. A comprehensive method allows us to carry out this research. It includes the study of the technical and planning parameters, the historical context and the comparative analysis of Norwegian cathedrals with monuments of different European architectural schools.The medieval cathedrals of Norway represent their own original way of the development of English and German medieval architectural traditions, including the Lombard one. It is proper to speak about the specificity of the Norwegian cathedrals as far as they are not the copies of European buildings. In our opinion, their unique character lies in a different construction environment. The masters who had a huge experience in erecting stone cathedrals came to Norway and faced certain conditions related to the preferences of customers, local climate features, and national culture. The uniqueness of each cathedral proves that Norwegian church architecture is a special phenomenon in the history of art.